Analisis Waste Inventory pada Proses Pengelolaan Persediaan Buku di PT. XYZ - Zaidan Edya Putra Musdhary Adjie; Wiku Larutama (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The printing industry faces challenges in inventory management due to fluctuating demand and changing consumer preferences. One of the main problems that arises is inventory waste, which leads to increased storage costs and decreased operational efficiency. This study aims to analyze the causes of inventory waste in the inventory management process at PT. XYZ. The research method used is a descriptive qualitative approach, with data collected through observation, interviews, and document analysis. The analysis was conducted using a fishbone diagram by classifying causal factors into human resources, methods, materials, and environmental aspects. The results indicate that inventory waste is triggered by production decisions made before payment certainty, the implementation of a push system, the short life cycle of book products, and fluctuating market demand. As a solution, this study proposes the application of Lean Logistics principles through a pull system, periodic inventory control, and the 5S method to reduce inventory waste.